The effectiveness and acceptability of evidence synthesis summary formats for clinical guideline development groups: a mixed-methods systematic review - Melissa K. Sharp; Dayang Anis Binti Awang Baki; Joan Quigley; Barrie Tyner; Declan Devane; Kamal R. Mahtani; Susan M. Smith; Michelle O’Neill; Máirín Ryan; Barbara Clyne (Implementation Science, 2022)
Abstract Introduction Clinical guideline development often involves a rigorous synthesis of evidence involving multidisciplinary stakeholders with different priorities and knowledge of evidence synthesis; this makes communicating findings complex. Summary formats are typically used to communicate the results of evidence syntheses; however, there is little consensus on which formats are most effective and acceptable for different stakeholders. Methods This mixed-methods systematic review (MMSR) aimed to evaluate the effectiveness and acceptability (e.g. preferences and attitudes and preferences towards) of evidence synthesis summary formats for GDG members. We followed the PRISMA 2020 guideline and Joanna Briggs Institute Manual for Evidence Synthesis for MMSRs. We searched six databases (inception to April 20, 2021) for randomised controlled trials (RCTs), RCTs with a qualitative component, and qualitative studies. Screening, data extraction, and quality appraisal were performed in duplicate. Qualitative findings were synthesised using meta-aggregation, and quantitative findings are described narratively. Results We identified 17,240 citations and screened 54 full-text articles, resulting in 22 eligible articles (20 unique studies): 4 articles reported the results of 5 RCTs, one of which also had a qualitative component. The other 18 articles discussed the results of 16 qualitative studies. Therefore, we had 5 trials and 17 qualitative studies to extract data from. Studies were geographically heterogeneous and included a variety of stakeholders and summary formats. All 5 RCTs assessed knowledge or understanding with 3 reporting improvement with newer formats. The qualitative analysis identified 6 categories of recommendations: ‘presenting information’, ‘tailoring information’ for end users, ‘trust in producers and summary’, ‘knowledge required’ to understand findings, ‘quality of evidence’, and properly ‘contextualising information’. Across these categories, the synthesis resulted in 126 recommendations for practice. Nine recommendations were supported by both quantitative and qualitative evidence and 116 by only qualitative. A majority focused on how to present information (n = 64) and tailor content for different end users (n = 24). Conclusions This MMSR provides guidance on how to improve evidence summary structure and layout. This can be used by synthesis producers to better communicate to GDGs. Study findings will inform the co-creation of evidence summary format prototypes based on GDG member’s needs. Trial registration The protocol for this project was previously published, and the project was preregistered on Open Science Framework (Clyne and Sharp, Evidence synthesis and translation of findings for national clinical guideline development: addressing the needs and preferences of guideline development groups, 2021; Sharp and Clyne, Evidence synthesis summary formats for decision-makers and Clinical Guideline Development Groups: A mixed-methods systematic review protocol, 2021).